Optimal Control of the Ill-Posed Cauchy Elliptic Problem - A. Berhail; A. Omrane (International Journal of Differential Equations)
We give a characterization of the control for ill-posed problems of oscillating solutions. More precisely, we study the control of Cauchy elliptic problems via a regularization approach which generates incomplete information. We obtain a singular optimality system characterizing the no-regret control for the Cauchy problem.